The Oxford handbook of post-Keynesian economics. Volume 2, Critiques and methodology - Harcourt, Geoffrey Colin; Kriesler, Peter (New York : Oxford University Press, 2013)
This volume analyses Keynesian foundations of post-Keynesian economics, focusing on how uncertainty and liquidity revoke Say's law. It explains the key features of Michal Kalecki's analysis of a capitalist economy and examines his macroeconomics in the short-run. It also provides a brief overview of post-Keynesian contributions to the study of the economic problems of least developed countries, also known as development economics.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on November 15, 2013).
Keywords: Keynesian economics; Economics -- History -- 20th century; Economics -- History -- 21st century